Does residue cover lead to greater frost damage in barley under conservation agriculture? - Fonteyne, Simon; Rojas Cruz, Juan Manuel; Espinosa Solorio, Avelino; Honsdorf, Nora; Saldivia Tejeda, Abel; Guera, Ouorou Ganni Mariel; Verhulst, Nele (International Maize and Wheat Improvement Center, 2023)
Farmers reported increased frost damage in barley (Hordeum vulgare) sown in conservation agriculture in the Mexican Bajío region during the autumn-winter season. To determine whether this effect is real and whether it reduced crop yield under conservation agriculture, we performed two field experiments and gathered observational data from other experiments and farmers’ fields. Although more frost damage can sometimes indeed be observed in wheat and barley sown in permanent beds with stubble cover, the data indicate that the plants recover from this damage and that it does not affect yield. Frost damage should not be considered an impediment to adoption of conservation agriculture in the crops grown in the autumn-winter season in the Mexican Bajío.